CREATION OF PIPE-MILL PRODUCTION AT THE REPUBLIC UNITARY ENTERPRISE “BELORUSSIAN METALLURGICAL WORKS” - A. V. Gontarj; O. M. Lazjko; G. Ja. Shilenko (Литьë и металлургия)
Montage and arrangement of equipment for the seamless hot-rolled pipes production is being carried out at present at RUP ‘"BMZ”. The planned date of putting into operation of production is till July, 3, 2007.